2012
DOI: 10.2306/scienceasia1513-1874.2012.38.331
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation pattern of heavy metals in marine organisms collected from a coal burning power plant area of Malacca Strait

Abstract: Nowadays, the marine environment is becoming vulnerable because of anthropogenic pollutants such as heavy metals carried by small particles of fly ash generated by coal burning power plants. Toxic heavy metals such as Cd, Cu, Zn, Pb, and Cr were estimated in three types of marine organisms, i.e., Arius maculatus, Penaeus merguiensis, and Anadara granosa, collected from a coal burning power plant area of Malaysia. An independent-sample t-test was conducted to compare the metal concentration in analysed species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…The presence of trace metals and hydrocarbons in the tissues of fish sampled therefore indicates allocthonous input of pollutants from industrial and artisanal sources proximal to the creek. Both local (Olowu et al, 2010;Oladele and Jenyo-Oni, 2015) and foreign researchers (Ikem et al, 2003;Alam et al, 2012) have observed that contaminants are introduced into aquatic ecosystems through many routes and sources such as industrial, domestic, municipal run-offs and leachates. Alam et al (2012) and Akan et al (2012) had also reported that effluents generated by various processes in factories and discharged untreated into nearby water bodies may affect water quality and may result in dramatic changes in the chemical quality of the water.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of trace metals and hydrocarbons in the tissues of fish sampled therefore indicates allocthonous input of pollutants from industrial and artisanal sources proximal to the creek. Both local (Olowu et al, 2010;Oladele and Jenyo-Oni, 2015) and foreign researchers (Ikem et al, 2003;Alam et al, 2012) have observed that contaminants are introduced into aquatic ecosystems through many routes and sources such as industrial, domestic, municipal run-offs and leachates. Alam et al (2012) and Akan et al (2012) had also reported that effluents generated by various processes in factories and discharged untreated into nearby water bodies may affect water quality and may result in dramatic changes in the chemical quality of the water.…”
Section: Discussionmentioning
confidence: 99%
“…BSAF is a parameter which describes the accumulation of sediment in associated organic compounds or metals into the tissues of ecological receptors (Alam et al, 2012). Based on the BSAF calculated average values for the present study, the metals are ordered as Cd (0.202) 4Cu (0.072) 4Pb (0.042) 4Zn (0.032) 4Ni (0.013) 4Cr (0.004) 4Mn (0.001) 4Fe (0.0015) respectively.…”
Section: Biota Sediment Accumulation Factor (Bsaf)mentioning
confidence: 99%
“…The BSAF is a parameter which describes the accumulation of sediment-associated organic compounds or metals into tissues of ecological receptors [35]. In this study, the efficiency of metal bioaccumulation in Corallina officinalis was evaluated by calculating the BSAF, which is defined as the ratio between the metal concentration in organisms and that in the sediment [8].…”
Section: Discussionmentioning
confidence: 99%